Music therapy and traumatic brain injury a light on a dark night - Gilbertson, Simon; Aldridge, David (Jessica Kingsley Publishers, 2008)
Gilbertson and Aldridge demonstrate how music therapy can be used to attend to the holistic, rather than purely functional, needs of people affected by severe head trauma. This book will give clinicians key notes for practice and a vision of the integral role music therapy can have in the successful rehabilitation from brain injury.
Keywords: Brain damage : Patients : Rehabilitation : Case studies; Music therapy : Case studies